Transmissible venereal tumor in a dog: Case report (Research, Society and Development, 2024)
Transmissible Venereal Tumor (TVT) is a highly contagious round-cell neoplasm of mesenchymal origin, typically sexually transmitted, that primarily affects the external genitalia of dogs, more frequently in intact males and females. The objective of this study was to report the case of a two-year-old mixed-breed female dog, treated at a veterinary clinic in Rio de Janeiro, presenting with perivulvar alterations compatible with TVT. The diagnosis was confirmed through vulvar cytology, which revealed the presence of typical round cells characteristic of TVT. Treatment was carried out using vincristine sulfate, a chemotherapeutic agent, and after two cycles, complete remission of the lesion was achieved. During the treatment, the patient developed leukopenia, a common complication of chemotherapy, which was managed with immunomodulators, allowing the therapeutic protocol to continue. The prognosis was favorable, with the patient clinically healthy at the end of the treatment. This study highlights the importance of early diagnosis and hematological monitoring during chemotherapy to ensure its effectiveness and minimize adverse effects.